2020
DOI: 10.1016/j.prostaglandins.2019.106386
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 PUFA improved tubular function after ischemia induced acute kidney injury in mice but did not attenuate impairment of renal function

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 100 publications
(159 reference statements)
2
15
0
Order By: Relevance
“…The present study found that the administration of omega-3 PUFAs significantly decreased BUN, Cr, and K and increased urine volume in ICU patients infected with COVID-19. These findings suggest that omega-3 supplementation may be protective against progression to renal impairment, consistent with observations from animal models that showed that omega-3 PUFA supplementation reduces the progression of renal disease [27][28][29][30][31]. Moreover, studies in human subjects suggested that a higher dietary intake of PUFAs may improve creatinine clearance [32] and also may have a role in maintaining healthy kidney function [33].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study found that the administration of omega-3 PUFAs significantly decreased BUN, Cr, and K and increased urine volume in ICU patients infected with COVID-19. These findings suggest that omega-3 supplementation may be protective against progression to renal impairment, consistent with observations from animal models that showed that omega-3 PUFA supplementation reduces the progression of renal disease [27][28][29][30][31]. Moreover, studies in human subjects suggested that a higher dietary intake of PUFAs may improve creatinine clearance [32] and also may have a role in maintaining healthy kidney function [33].…”
Section: Discussionsupporting
confidence: 84%
“…Higashihara et al assessed the effects of omega-3 PUFAs on kidney function in 41 patients with stages two or three chronic kidney disease (CKD); omega-3 supplementation did not alter kidney function, assessed using 24-h urine creatinine clearance. Another study demonstrated that omega-3 PUFA pretreatment did not protect against renal function deterioration or ischemia-induced renal inflammation; however, tubular transport was improved [30]. Previous studies that have evaluated omega-3 PUFAs in the treatment of kidney disease have yielded contradictory results, which may reflect differences in study duration, dosage of omega-3, route of administration, and type of omega-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Rund et al [ 36 ] administered dietary omega-3 polyunsaturated fatty acid (n3-PUFA) supplementation to male mice, before inducing renal ischemia. Omega-3 polyunsaturated fatty acids caused an upregulation of HO-1, but this did not affect overall renal function and inflammation.…”
Section: Ischemia-reperfusion Injury (Iri)mentioning
confidence: 99%
“…The increased expression of HO-1 has been suggested to play a key cytoprotective role in maintaining the redox homeostasis and activating the oxidative stress defense mechanism when cells are subjected to certain types of stress, such as inflammation, ischemia, hypothermia or radiation exposure (7). HO-1 was discovered to be induced in response to renal IRI (8)(9)(10), and to prolong renal allograft survival, reduce renal tubular damage induced by IRI and improve renal function (11,12).…”
Section: Introductionmentioning
confidence: 99%